Debating Toynbee's theory of challenge and response: Christian civilisation or Western imperialism? - F. Hale (Acta Theologica)
In his 1952 Reith Lectures on the British Broadcasting Corporation, “The World and the West”, the eminent London historian Professor Arnold Toynbee sought to explain inter alia why western European hegemony over much of the world was widely resented. His interpretation incorporated the “challenge and response” theory of successive civilisations which underlay his multi-volume A  Study of History. Toynbee’s lectures drew sharp criticism from many quarters, not least because he gave the impression that the era of Western hegemony was waning and that much of the  momentum of world history was moving to the East. This in itself was a controversial perception in the Cold War. In some Christian circles, his overarching interpretation was rejected as  historiographically flawed. In the ensuing debate, the prominent English Roman Catholic historian and publisher Douglas Jerrold argued in his The Lie about the West: A Response to Professor  Toynbee’s Challenge that he had unjustly underestimated the endurance of Christian civilisation and failed to recognise its inherent value as the source of many fundamental values which should  not be surrendered to supposedly inexorable historical processes.